Statistical Distribution As Predictive Tool - Irawan Wingdes (JUDIMAS, 2020)
Statistics is an important aspect in data presentation and usage. This community engagement activity was held with the cooperation of SMA Negeri IV and STMIK Pontianak. The purpose of the activity was to enrich students in basic statistics understanding, usage of normal distribution for prediction, and implementation of normal distribution in daily setting. The community engagement activity was held with seminar and discussion method. Software utilised are Microsoft Excel, Microsoft Power Point with hardwares such as LCD projector, whiteboard, and loudspeaker. The seminar are participated by 34 students from xi grade. The result of the seminar was as expected, with participants understood the statistic tools usage and was able to implement normal distribution for prediction purpose.